Analisis Eksistensi Gereja HKBP Laut Dendang di Desa Laut Dendang - Geubrina, Pocut Puan; Sinurat, Ester; Pandiangan, Errason; Hutagalung, Galatia Valentin; Dachi, Grace Holyvia Juniadsari; R, Rohani; Kardiana, Elsa (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Conflicts and violence in the name of religion in Indonesia continue to increase from year to year. One of the issues that often disrupts harmonious relations between religious communities is the issue related to the establishment of houses of worship. This problem arises because there is a thin line between the right to worship and the right to establish a house of worship. Some religious groups may view the right to establish a house of worship as the same as an inviolable personal right. In fact, the matter of establishing a house of worship is actually a collective social realm. Establishing a house of worship in an inappropriate location or environment can result in discomfort or disturbance from other parties. Prolonged discomfort can lead to hatred and hostility. This study focuses more on the results of the continuation of the problem regarding the establishment or repair of a Christian house of worship at the HKBP Lau Dendang Church In Lau Dendang Village. The results of the study show that the HKBP Laut Dendang Church plays an active role in community life. The church not only functions as a place of worship, but also as a center for social, educational, and cultural activities for the congregation and the surrounding community. There are obstacles in understanding and communication between the congregation and the church, which can lead to misunderstandings, conflicts, and imbalances in church life. Therefore, efforts are needed to improve communication, understanding, and congregation participation so that the church can function well and provide the best services.